Millstone Exfoliation: a True Shear Exfoliation for Large-Size Few-Layer Graphene Oxide - Heng-Ju Yoon; Jae Young Lee; Tae-Ho Yoon (Nanoscale Research Letters, 2018)
Abstract A millstone (MS) was introduced in the production of large-size few-layer-graphene oxide (FLGO) via true shear exfoliation in order to minimize fragmentation. The MS was constructed with two glass plates, where the top plate was designed to rotate against the stationary bottom plate, thereby generating true shear force. Mildly oxidized graphite (MOG) was used for MS exfoliation in order to obtain both good property and high yield. The rpm of rotation (10, 20, 30, 40, and 50), solution concentration (0.5, 1, and 2 mg/ml), and number of exfoliation (1, 2, and 3) were optimized by measuring the UV-vis absorption, and the effect of oxidation time (30, 60, and 90 min) was studied under the given optimum conditions. Next, the FLGO was isolated by centrifugation and characterized by TEM and AFM. The FLGO obtained was as large as ~ 10 μm in size, which was slightly smaller than the pristine graphite, suggesting a possibility of slight fragmentation. But it was still much larger than the FLGO obtained via sonication (< 1 μm), demonstrating successful MS exfoliation.